STUDI FASIES DAN PEMODELAN RESERVOIR STATIS PADA INTERVAL FS 2 - FS 10 FORMASI CIBULAKAN ATAS, LAPANGAN SEKIP, CEKUNGAN CIPUNEGARA, JAWA BARAT - Salsabila Tanjung, Jauhar
Sekip Field is one of the oil and gas fields in the ONWJ Block, North West Java Basin, West Java. This field is currently considered as a development field within coverage area approximately 100 km2. The study was conducted at FS 2 - FS 10 intervals which are part of the Upper Cibulakan Formation. There are four reservoirs to be focused on this study. The study was conducted to determine depositional and facies environments, formation evaluation and distribution of petrophysical properties, and subsurface mapping to determine reservoir geometry. The estimation of hydrocarbon reserves is carried out to determine the amount of Original Oil in Place (OOIP) and Original Gas in Place (OGIP). The data used in this study consisted of core data, and well logs from 33 wells in the study area. The results of the core analysis showed that FS 2 - FS 10 compiler intervals were six sandstone lithofacies namely F1, F2, F3, F4, F5, and F6, one claystone facies namely F7 and one limestone facies, F8. Based on core, ichnofossil and electrofacies analysis, the depositional environment is transgressive tidal ridge depositional environment in the age of Middle Miocene. Facies associations consist of AF1 (Tidal Dominant Lower Shoreface), AF2 (Tidal Dominated Upper Shoreface), and AF3 (Transgressive Lower Shoreface) with maps of reservoir geometry thickness, ridge, with reservoir geometry maps of sand ridges presents a NE-SW general trend of sedimentation. Furthermore, static reservoir modeling is performed to model facies and petrophysics. Distribution of petrophysical properties given effective porosity, permeability, and water saturation is qualitatively controlled by the distribution of facies with Northeast - Southwest. The estimated reserve results show volumes from the Reservoir 1 interval of 3.22 BCF of gas and 3.96 MMBL of oil, Reservoir 2 of 0.90 BCF of gas and 0.49 MMBL of oil, Reservoir 3 of 0.14 BCF of gas and 1.89 MMBL oil, and Reservoir 4 of 2.69 BCF of gas and 1.89 MMBL of oil.